(3OjhGf GdJgGeis - (3Ydj Hf eMeO Hf agO, CHh GdMSf GdJgGej,J (B416 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf Ydi Hf eMeO GdJgGei QMeg Gddg JYGdi jeOM GdCejQ fUQ GdOhdI eQhGf HejG aGQbjf (B: (3YHS ef TYQ ai GdQCS eQJSe eGfaQ GdHjV eKd GdHjV ai Gdceje s
(3BNQgG (B:s
(3dGjbJfi GdYdjGA EdG HGdXHi (B: (3bOekG EPG s
(3HgG fXGe GdJYbjHIs
(3ZjQ eQJH Ydi GdbhGai Ch GdehVhYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B219s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdCOHs